THE ROLE OF HUMAN RESOURCE CAPACITY IN ENHANCING THE QUALITY OF COMMUNITY-BASED TOURISM VILLAGE MANAGEMENT: EVIDENCE FROM SRAGEN, INDONESIA - Tri Wartono; Adya Hermawati; Oneng Setya Harini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the effect of human resource (HR) capacity on the quality of community-based tourism (CBT) village management in Sragen Regency, Indonesia. The background of this research is based on the important role of human resources in supporting successful village tourism management, particularly in addressing the transition from an agriculture-based economy to a more professional and sustainable tourism sector. Although the CBT concept emphasizes community participation, the quality of village tourism management still faces challenges related to limited local human resource capacity.This research employs a quantitative approach with descriptive and verification design. Data were collected through structured questionnaires from 195 respondents consisting of village tourism managers, village officials, and local communities in Sragen Regency, selected using simple random sampling. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with SmartPLS version 4 to examine the relationships between the research variables.The results indicate that human resource capacity has a positive and significant effect on the quality of CBT village tourism management. This finding suggests that improvements in knowledge, skills, experience, and managerial capabilities of local communities play a crucial role in enhancing the effectiveness of tourism village management. Furthermore, human resource capacity is proven to be a key determinant in supporting participatory, professional, and sustainable village tourism management.This study implies that strengthening human resource capacity through education, training, and community empowerment should be prioritized in the development of village tourism. Therefore, the findings are expected to serve as a reference for local governments and tourism managers in formulating more effective and sustainable community-based tourism development strategies.